A Rhetorical Analysis of Denise Levertov's "From a Notebook: October '68 May '69" - Phillips, Jean. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Defninig rhetorical analysis as a means of studying writer/audience relationships allowing both intrinsic and extrinsic analysis, the author discusses the three sections of Levertov's poem, "From a Notebook: October '68--May '69." Section 1 is the speaker's personal comparison of her associations with life and death, comparison of herself to literary personae, and a view of her age and education as preparation for the revolutionary commitment she has made. Section 2 is a more personal and philosophical underpinning of the speaker's commitment. The third section finalizes the speaker's definition of revolution: the antithesis of death, the counterpart of life. The poem is then examined in relation to Levertov's biography and as a process of the speaker's working through language to the committed stand toward revolution which she finally adopts and acts on. (TS)
ERIC Note: Paper given at the Speech Communication Association. Spring Doctoral Honors Seminar in Interpretation (Northwestern University, Evanston, Illinois, May 1973).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Analytical Criticism; Authors; Content Analysis; Critical Reading; Interpretive Reading; Literary Criticism; Oral Interpretation; Poetry; Rhetorical Criticism; Textual Criticism; Levertov (Denise); Speeches/Meeting Papers